Iamblichus : On the Pythagorean Life - Iamblichos, asi 250-asi 330 (Translated texts for historians ;, 1989)
The Pythagorean Life is the most extensive surviving source on Pythagoreanism, and has wider interest as an account of the religious aspirations of late antiquity.